2015
DOI: 10.1101/030569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

4C-ker: A method to reproducibly identify genome-wide interactions captured by 4C-Seq experiments

Abstract: Abstract4C-Seq has proven to be a powerful technique to identify genome-wide interactions with a single locus of interest (or "bait") that can be important for gene regulation. However, analysis of 4C-Seq data is complicated by the many biases inherent to the technique. An important consideration when dealing with 4C-Seq data is the differences in resolution of signal across the genome that result from differences in 3D distance separation from the bait. This leads to the highest signal in the region immediate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
(30 reference statements)
0
23
0
Order By: Relevance
“…Bait-specific primers for the circularized inverse PCR are listed in Supplemental Table S7. Amplicons were sequenced on a HiSeq2500 platform (Illumina), mapped to the reference genome (hg19) and analyzed with the Hidden-Markov-Model-based tool 4Cker (Raviram et al 2016). This tool corrects for increasing signal noise in trans chromosomal interactions and far-cis chromosomal interactions by adaptive window sizes.…”
Section: Circular Chromatin Conformation Capture (4c)mentioning
confidence: 99%
“…Bait-specific primers for the circularized inverse PCR are listed in Supplemental Table S7. Amplicons were sequenced on a HiSeq2500 platform (Illumina), mapped to the reference genome (hg19) and analyzed with the Hidden-Markov-Model-based tool 4Cker (Raviram et al 2016). This tool corrects for increasing signal noise in trans chromosomal interactions and far-cis chromosomal interactions by adaptive window sizes.…”
Section: Circular Chromatin Conformation Capture (4c)mentioning
confidence: 99%
“…Sequencing library was prepared as described using Expand Long Template polymerase (Roche) and Illumina adaptor sequence-containing primers unique to the hTERT fragend listed in Supplementary Table 1. Sequencing was performed by the NYU Genome Technology Core on Illumina HiSeq 4000 sequencer. Sequencing data was analyzed using the 4Cker software package described in (14) using the recommended parameters.…”
Section: C and Atac-seq Genome-wide Sequencing And Bioinformatic Anamentioning
confidence: 99%
“…Active REs are known to directly contact the promoters they regulate and have increased chromatin accessibility, we therefore, performed Circular Chromosomal Conformation Capture (4C) and ATAC-seq in H7 human embryonic stem cells (ESC) and adult retinal pigment epithelial (ARPE) cells that are proficient for p53 and have a stable diploid karyotype. We used a 1.1 kb fragment spanning the hTERT promoter as bait and captured sequences that are in close proximity by 4C (13), using 4Cker software to analyze Illumina sequencing reads (Figure S1B-C) (14). Our analysis identified loci that contact the hTERT promoter exclusively in telomerase positive cells (H7) or in telomerase negative cells (ARPE), as well as loci that contact the TERT promoter in both cases.…”
mentioning
confidence: 99%
“…Visual inspection of the interactions of this RLTR4 copy with the rest of the genome, revealed that the regions of higher interaction belonged to the A compartment. The 4C-ker pipeline [60] was used to quantify this and determine which regions on chromosome 3 interact at high frequency with the MuLV integration site. As shown in Fig.…”
Section: Erv Interactions Are Constrained By the Compartments And Locmentioning
confidence: 99%
“…Single-end reads were mapped to a reduced genome of unique 25bp fragments adjacent to DpnII sites (mm10) using bowtie2 [79] as per the details described in 4C-ker [60]. Reads that map to the Encode blacklist regions were removed from downstream analysis [80].…”
Section: Tran-pcr Analysismentioning
confidence: 99%